An anti-perfringolysin O monoclonal antibody cross-reactive with streptolysin O protects against streptococcal toxic shock syndrome - Matsumura, Takayuki; Nishiyama, Ayae; Aiko, Michio; Ainai, Akira; Ikebe, Tadayoshi; Chiba, Joe; Ato, Manabu; Takahashi, Yoshimasa (BMC research notes, 2020)
Streptococcus pyogenes (Group A Streptococcus; GAS) causes a variety of infections that include life-threatening, severe invasive GAS infections, such as streptococcal toxic shock syndrome (STSS), with > 30% mortality rate, despite effective antibiotics and treatment options. STSS clinical isolates highly express streptolysin O (SLO), a member of a large family of pore-forming toxins called cholesterol-dependent cytolysins (CDCs). SLO is an important toxic factor for GAS and may be an effective therapeutic target for the treatment of STSS. Our aim was to identify a monoclonal antibody (mAb) that reacts with SLO and has therapeutic potential for STSS treatment. We focused on mAbs that had originally been established as neutralizing reagents to perfringolysin O (PFO), another member of the CDC family, as some cross-reactivity with SLO had been reported. Here, we confirmed cross-reactivity of an anti-PFO mAb named HS1 with SLO. In vitro analysis revealed that HS1 mAb sufficiently prevented human neutrophils from being killed by STSS clinical isolates. Furthermore, prophylactic and therapeutic injection of HS1 mAb into C57BL/6 mice significantly improved the survival rate following lethal infection with an STSS clinical isolate. These results highlight the therapeutic potential of HS1 mAb for STSS treatment.